Digital photography for the analysis of fluorescence responses - Schwaebel, S. Thimon; Trapp, Oliver; Bunz, Uwe H. F. (Chemical science, 2013)
Different pyridine substituted cruciform fluorophores (XF) were prepared and their optical properties were studied. Upon protonation of the pyridine nitrogen, the XFs with a para or ortho substitution pattern show similar bathochromic shifts in the emission, whereas the meta XF features a smaller bathochromic shift in emission wavelength. The color changes of XFs in the presence of carboxylic acids were used to identify them by digital photography. Data extraction of the photographs is performed by a combination of a large RGB color space, a standard white balance, the transformation of RGB values into u′v′ values and MANOVA statistics, improving the recognition of analytes by pyridine XFs. We discuss in this paper factors that determine the quality of the extraction of color information from digital photograph.
First published: 17 Oct 2012
Gesehen am 09.08.2021